i have two questions, for both i need to find F'(x) of the function.

i think both are using the product rule but not 100% certain. All help much appreciated.

1 f(x)= ln(x^3-1/3x^2)

2 f(x)=e^cosx *sin(ln x)

Printable View

- Jun 29th 2008, 01:31 AMolliemanDifferential calculus
i have two questions, for both i need to find F'(x) of the function.

i think both are using the product rule but not 100% certain. All help much appreciated.

1 f(x)= ln(x^3-1/3x^2)

2 f(x)=e^cosx *sin(ln x) - Jun 29th 2008, 01:59 AMwingless
1. Use chain rule and quotient rule.

2. Use chain rule and product rule. - Jun 29th 2008, 02:28 AMSimplicity

1.

$\displaystyle f(x)= \ln \left( \frac{x^3-1}{3x^2}\right)$

Using the log rules: $\displaystyle \ln \left(\frac{a}{b}\right) = \ln (a) - \ln(b)$

$\displaystyle f(x)= \ln \left( x^3-1\right) - \ln (3x^2)$

$\displaystyle \ln$ is given if in a fraction, the denominator differentiated gives the numerator. $\displaystyle \ln x = \int \frac{1}{x}$

$\displaystyle f'(x) = \frac{3x^2}{x^3-1} - \frac{6x}{3x^2}$

2.

$\displaystyle f(x)=e^{\cos x} *\sin(\ln x)$

$\displaystyle u = e^{\cos x}, \ u' = -\sin x . e^{\cos x}, \ v= \sin(\ln x), \ v' = \frac{\cos(\ln (x))}{x}$

$\displaystyle \frac{\mathrm{d}(uv)}{\mathrm{d}x} = uv' + u'v$

$\displaystyle f'(x) = (e^{\cos x})\left(\frac{\cos(\ln (x))}{x}\right) + (-\sin x . e^{\cos x})(\sin(\ln x))$ - Jun 29th 2008, 03:10 AMnikhilCheck this out
Hi!ollieman

Chain rule should be used for sureand

I will solve one of the question

as an example.(you may do other one by urself,ask if you have any doubt in solving)

y=f(x)=[e^cosx]sin(ln(x))

differentiating we get

y'=[d/dx(e^cosx)]sin(ln(x))+[e^cosx]d/dx(sin(lnx))

y'=[d/dx(e^cosx)]sin(ln(x))+[e^cosx]cos(lnx)d/dx(lnx)

y'=[d/dx(e^cosx)]sin(ln(x))+[e^cosx]cos(lnx)(1/x)

we may solve [d/dx(e^cosx)] saperately as it is a power function

let A=e^cosx

lnA=cosx

1/A(dA/dx)=-sinx

dA/dx=-sinx*A=-e^cos(x)[sin(x)]

so finally

y'= -[e^cos(x)]sin(x)sin(lnx)+[e^cosx]cos(lnx)(1/x)